Radiosensitivity Analysis in Cucumis sativus L. - Raju K M (Department of Agricultural Botany, College of Agriculture, 1994)
The effect of five doses of gamma rays viz. 10, 20, 30, 40 and 50 kR in ten Cucumis sativus L. varieties was studied in M1 generation. Enhanced germination was observed in some varities in laboratory condition whereas in field condition a reduction in germination percentage was noticed in all treatments compared to control. Reduced survival percentage as a result of gamma irradiation was noticed on 40th day after sowing. Morphological abnormalities such as leaves with short petioles, half leaf blade only and chlorophyll deficient patches were obtained as a result of gamma irradiation. Increased sex ratio as a result of gamma irradiation was noticed in the present study. No variation was noticed on floral morphology. Variations in fruit morphology, reduced fruit weight and mean yield per plant were observed in certain treatments. Gamma irradiation increased pollen sterility. Cytological aberration were not observed in the present investigation. Different varieties of Cucumis sativus L. showed differential response to gamma rays. The characters studied in the M1 generations indicate the scope for selection of beneficial mutants in the segregating generations.